Pengaruh Pemberian Ransum dengan Kualitas Berbeda Terhadap Profil Darah, Produksi Susu dan Pertambahan Bobot Badan Sapi Perah - Hanifa, Aqni (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2008)
An experiment was conducted to study blood profile, milk yield and liveweight gain of dairy cows as affected by dietary different quality of diets. The experiment used 15 lactating PFH were assigned into three treatments of diets and  five replication, three treatments of diets were : 1) T1 (CP 12% dan TDN 65%); 2) T2 (CP 14% dan TDN 70%) dan 3) T3 (CP 16% dan TDN 75%).The results of this experiment showed that the average of dry matter (DM) intake on Tl, T2 and T3 treatments were 8,59; 10,03 and 10,94 kg/d, respectively (P<0,01). The average of crude protein intake (CP) on T1, T2 and T3 treatments were 1,06; 1,44 and 1,71 kg/d (P<0,01), also the average of TDN intake on T1, T2 and T3 treatments were 5,52; 6,86 and 8,02 kg/d (P<0,01). The average of Hemoglobin (Hb) concentration on T1, T2 and T3 treatments were 10,21: 11,18 and 10,44 g/dl (P>0,05), also the average of eritrosit value on TI, T2 and T3 treatments were 3,37; 3,73 and 3,48 million/mm3;, respectively (P>0,05). The average of milk yield on T1, T2 and T3 treatments were 8,12; 11,29 and 13,42 l/d (P<0,05). The average of liveweight gain on TI, T2 and T3 treatments were 81,66; 117,71 and 320,00 g/d (P>0,05). The conclusions of this research was the highest level of CP and "1'DN in diets (CP 16% and TDN 75%) showed that feed intake (DM, CP and TDN) and milk yield gave the best than other treatments. Different dietary quality of diets altered significant on feed intake (DM, CP and TDN) and milk yield, but the treatments did not affect on liveweight gain, Fib and eritrosit concentration. Key words :     diets quality, feed intake, blood profile, milk yield, liveweight gain, dairy cows